Effect of thermal treatment on the structural characteristics and electrochemical properties of amorphous Mn oxide prepared by an ethanol-based precipitation method - Kim, Nam Dong; Yun, Hyeong Jin; Nam, Inho; Song, In Kyu; Yi, Jongheop (Current applied physics, 2012)
Nanostructured amorphous Mn oxide, for use as an electrode material in supercapacitors, was prepared by a facile precipitation method using ethanol. After thermal treatment at various temperatures, the structural characteristics and electrochemical properties of the prepared Mn oxide were investigated. Importantly, the experimental results revealed that the alkyl chain of ethanol prevented the excessive crystallization of Mn oxide, resulting in the production of nanostructured Mn oxide. In addition, electrochemical properties of synthesized material were highly dependent on the structural characteristics. Mn oxide thermally treated at 300 °C, which had an optimized crystalline structure, showed the highest specific capacitance of 161 F/g in this study. ► Novel precipitation method to synthesize nanostructured Mn oxide, using ethanol as solvent. ► Effect of ethanol on crytallinity of a nanostructured Mn oxide was investigated. ► Crystallinity of Mn oxide can be controlled by adequate thermal treatment. ► Relationship among thermal treatment, crystallinity, and electrochemical performance was investigated. ► Optimum condition between degree of amorphous and electrochemical activity was found.